Mapping PTSD across the symptom spectrum: Affective, emotion regulation and cumulative trauma predictors in Syrian refugees: A quantile regression approach - Emre Han Alpay (British Journal of Clinical Psychology, 2026)
Abstract Objectives This study examined whether affective factors, emotion regulation strategies, cumulative trauma exposure, resilience and perceived social support are differentially associated with PTSD symptom severity across the symptom spectrum in Syrian refugees. Design Cross‐sectional study. Methods Participants were 461 adult Syrian refugees residing in Türkiye (M = 41.54, SD = 12.08), of whom 73.5% ( n = 339) were women. Quantile regression was used to examine whether associations with affective variables, emotion regulation strategies, cumulative trauma exposure, resilience and perceived social support varied across the PTSD symptom distribution. Results Depression and anxiety were associated with PTSD symptoms across all quantiles, indicating that transdiagnostic affective distress is a stable correlate across the severity continuum. By contrast, emotion regulation strategies showed heterogeneous associations across symptom levels. Cognitive reappraisal demonstrated a stronger inverse association with PTSD at higher symptom levels, whereas expressive suppression was more strongly associated with severe symptoms. Type II traumas, reflecting repeated relational and identity‐related adversities, were associated primarily with lower‐to‐moderate PTSD severity, whereas Type III traumas, reflecting chronic and ongoing stress exposure, were associated with moderate‐to‐severe symptom levels. Resilience and perceived social support were not independently associated with PTSD after accounting for emotional distress and cumulative trauma exposure. Conclusions The findings highlight the importance of considering symptom heterogeneity when examining PTSD in refugee populations. Emotion regulation processes and cumulative trauma exposure demonstrated severity‐specific associations, suggesting that assessment and intervention planning may benefit from considering where individuals fall along the PTSD symptom continuum rather than relying solely on average population‐level effects.